Economic stimulus packages : returning to growth : address - Bourne, Compton ([CDB] [St. Michael]BB, 2009)
Notes that the fiscal situation of most countries in the Americas and the Caribbean is a severe limitation on their capacity to implement economic stimulus packages of sizes warranted by their economic downturns. Consequently the countries that were represented at the Fifth Summit of the Americas must decide whether they have been adequately served by the decisions of the G20 Summit.